Measuring the Relationship between Crude Oil Price, Stock Market and Gold Price with Reference India - KP, Jaheer Mukthar; K, Sivasubramanian; V, Raju (International Journal of Finance Research, 2021)
India is one among the highly potential market for the oil consumption. When we are considering the industrial line, natural gas and oil industry, it portraits a great significant influence on the economic growth and development through the GDP and per capita flow of income. The year-wise statistics was collected for two decades from 2000 to 2019 and the everyday prices such as gold price, Nifty opinions and Crude oil prices are intended and taken the annual averages of it. The aim for selecting the data from the year 2000 to 2019 is very vital. It was selected to find out the influence of new financial policy 1991 after 10 years of its application. Moreover, the main implication of this work is to find the causal association among these financial variables. The price of gold is considered as 24 carat, the average price was taken for analysis. The ANOVA model has been applied to predict the relationship between the variables in order to find out the cause and effect.  It reveals the positive correlation between the variables. It is also revealed from the study that the price of gold had an exponential increase over a period of two decades and alongside the Nifty points also increased in the same period of time. On the whole, it is found from the data that the gold price is having the positive relation with Nifty points of the stock market and the crude oil price did not have any influence on the determination of gold price.